Hosting and Human Rights: The Summer Olympics in the Twenty-First Century - Ross, MacIntosh; McDougall, Michael (Frontiers in Sports and Active Living, 2022)
During the twenty-first century, Summer Olympic Games have been used to distract from, justify and push through acts of increased securitization, surveillance, and displacement of the host city populace. Situating sport within the field of International Relations, we outline these civil and human rights intrusions across successive Games. From Sydney 2000 to Rio de Janeiro 2016, we explicate the consequences, contestedness, and evolution of repressive techniques applied at each Games using theories of hegemony espoused by Antonio Gramsci, Robert W. Cox, and Raymond Williams, among others. In doing so, we demonstrate how the International Olympic Committee (IOC), their partners and host cities are wedded in a symbolic and symbiotic courtship that manufactures local consent for and normalizes human right infringements; simultaneously providing the architecture for the spread and imposition of neoliberal order on the citizenry, while masking the damage done by and through the Olympics. Finally, we close by asserting that the current formulation of the Olympics are not ‘the best we can do.' Instead, through the counterhegemonic potential of critical approaches and engaged, strategic action, a transformation of critical consciousness - and the Olympics, into something to be proud of - remain a live and entirely possible option.